الأحكام المتعلقة بالملكية العقارية الشائعة للأسرة - صابرة بشي, كريمة جاب الله (Universté ELOUEd-جامعة الوادي, 2022)
إن أحكام الشيوع كانت ولا ت ا زل من أهم الموضوعات التي أثارت جدلا كبي ا ر بين فقهاء القانون المدني، خاصة فيما يتعلق بطبيعة حق الشريك في الشيوع، ونظر للنتائج المهمة التي تترتب عليها، فقد أخذ المشرع حق ملكية بالمعنى التام، ومحل هذا الحق هو المال الشائع، نظ ا ر لتمتع الشركاء في الشيوع بنفس السلطات يؤدي إلى ت ا زحم بين حقوق الشركاء لأن كل تصرف يقوم أحدهم يمس مباشرة بحقوق الشركاء لذلك قيد المشرع ممارسة الشريك في سلطاته كمالك بعدم الاض ا رر بحقوق بقية الشركاء عن طريق وضع أحكام تنظم ملكية العقارية الشائعة وكيفية الإدارة والتصرف. أما بالنسبة لملكية الأسرة الغرض المخصص له المال الشائع لا يرجع إلى طبيعة المال او نم ا إلى الاتفاق حيث يتفق أعضاء الأسرة الواحدة على تكوين ملكية الأسرة غالبا ما يكون مصدرها الاموال الموروثة، وذلك في الحالات التي يستحسن فيها ترك الأموال دون قسمة، ولذا فهي لا تختلف عن الشيوع العادي، ويكم تطبيق أحكام إدارته عليها ولكن رغم ذلك خصها المشرع بقواعد خاصة، حيث أعطى للشركاء، حيث أعطي للشركاء الذين يملكون الأغلبية المطلقة للحصص فيها تعيين مدير المدير أو أكثر بينهم، وهذا الأخير رغم أنه معين من الأغلبية المطلقة إلى أن سلطاته واسعة تشمل بأعمال الإدارة المعتادة وغير المعتادة. الكلمات المفتاحية: أحكام، ملكية الأسرة، ملكية شائعة، انقضاء الشيوع.The provisions of communion were and still are one of the most important topics that aroused great controversy among civil law jurists, especially with regard to the nature of the partner’s right to communion, and in view of the important consequences that result from them, the legislator took a right of ownership in the full sense, and the place of this right is common money, given Because the partners in common enjoy the same powers, it leads to competition between the rights of the partners, because every action by one of them directly affects the rights of the partners. Therefore, the legislator restricted the partner’s exercise of his powers as an owner without harming the rights of the rest of the partners by setting provisions regulating the ownership of common real estate and how to manage and dispose of it. As for family ownership, the purpose for which common money is allocated is not due to the nature of money, but rather to the agreement, whereby members of the same family agree on the formation of family ownership, often the source of inherited money, in cases where it is desirable to leave the money undivided, and therefore it does not differ from common Ordinary, and the provisions of his management are applied to them, but despite that, the legislator singled them out with special rules, as he gave to the partners, where he was given to the partners who own the absolute majority of the shares therein the appointment of a manager or more among them, and the latter, although he is appointed from the absolute majority that his broad powers include the work of the management The usual and the unusual.
مذكرة الماستر
Keywords: أحكام، ملكية الأسرة، ملكية شائعة، انقضاء الشيوع.; provisions, family ownership, common ownership, extinction